KISAH DZULQARNAIN DALAM AL-QUR’AN SURAT AL-KAHFI: 83-101 (Pendekatan Hermeneutik) - Rukimin Rukimin (Profetika: Jurnal Studi Islam, 2014)
This article traces and tells the story of Dzulqarnain found in the HollyQur’an, it is due to the fact that this story is still covered by a mystery and unfinishedcontroversial understanding for Moslem Scholars since from the classic to contemporary era, even in the orientalism one. This study applies a library research with the Holly Qur’an and valid hadiths are as primary sources of data while the interpretation ofMoslem Scholars toward the verses telling the story of Dzulqarnain are as the secondarydata source. This study uses empiric-normative approach and the collected data are analyzed by using hermeneutic, namely: Schleiermacher grammatical hermeneutic andtheory of Muhammad Talbi humanistic-history. The result of the research shows thatthe grammatical sequences of the verses telling Dzulqarnain story has a very beautifullanguage style, completed with language style of Majaz in which the Dzulqarnain hasgone through two long journeys; they are Western and Eastern journeys. He got thefollowers from his journeys above. Moreover, based on the humanistic-historicallyreadability; first, the sequence of verses above shows that Islam is “RahmatanLil‘Alamin”. It can be proved from the wise attitude containing full goodness without anybullying, done by Dzulqarnain. Second, the denied followers are invited to have moreawareness and to go back to the right faith by warning them dealing with the statementthat says “Allah will give a finalization to the denying followers”.Key Words: Dzhulqarnain; the Holly Qur’an; hermeneutic.Artikel ini mentelusuri dan menguak kisah Dzulqarnain di dalam al-Qur’an,karena kisah ini masih diselimuti misteri serta kontroversial berkepanjangan di tubuhulama muslim sejak zaman klasik hingga kontemporer maupun di kalangan orientalis.Penelitian ini merupakan penelitian kepustakaan (library research), dengan sumber data primer adalah al-Qur’an dan hadits-hadits shahih, sedangkan sumber data sekunder adalah tafsir para ulama terhadap ayat-ayat yang menceritakan kisah Dzulqarnain.Pendekatan yang digunakan adalah normatif-empiris, analisisnya dengan hermeneutik, yakni hermeneutik gramatikal Schleiermacher dan teori historis-humanistik Muhammad Talbi. Hasil penelitian adalah rangkaian gramatikal dari ayat-ayat kisah tentang Dzulqarnain sangatlah indah gaya bahasanya disertai dengan gaya bahasa majaz, di mana Dzulqarnain telah menempuh dua perjalanan panjang yaitu perjalanan ke Barat dan ke Timur serta mendapatkan pada dua perjalanan tersebut segolongan kaum/umat.Pada perjalanan ke Barat (maghrib asy-syams). Lebih lanjut jika ditilik dari pembacaan secara historis-humanistik bahwasanya rangkaian ayat-ayat di atas menunjukkan Islam sebagai rahmatan lil ‘alamin. Hal ini dapat dibuktikan dari sikap bijak yang penuh kebaikan dan tanpa kekerasan yang ditonjolkan oleh Dzulqarnain, bahwasanya kepada umat yangingkar hendaknya diajak bertobat dan kembali kepada keimanan dengan diperingatkan akan kekufurannya bahwa Allah akan mengazab orang-orang yang ingkar.Kata Kunci: Dzhulqarnai; al-Qu’an; hermeneutika